2012
DOI: 10.1371/journal.pone.0040014
|View full text |Cite
|
Sign up to set email alerts
|

Web Search Queries Can Predict Stock Market Volumes

Abstract: We live in a computerized and networked society where many of our actions leave a digital trace and affect other people’s actions. This has lead to the emergence of a new data-driven research field: mathematical methods of computer science, statistical physics and sociometry provide insights on a wide range of disciplines ranging from social science to human mobility. A recent important discovery is that search engine traffic (i.e., the number of requests submitted by users to search engines on the www) can be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
152
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(159 citation statements)
references
References 33 publications
6
152
1
Order By: Relevance
“…6(b), the probability distribution ofF k (t) is obviously asymmetric with a heavier positive tail. This result indicates that the external information usually drives the market to be more active, which is consistent with the previous empirical findings for the internet query data or news [35,32].…”
Section: Information Driving Forcessupporting
confidence: 91%
See 1 more Smart Citation
“…6(b), the probability distribution ofF k (t) is obviously asymmetric with a heavier positive tail. This result indicates that the external information usually drives the market to be more active, which is consistent with the previous empirical findings for the internet query data or news [35,32].…”
Section: Information Driving Forcessupporting
confidence: 91%
“…In recent years, exploring the scientific impact of online big-data has attracted much attention of researchers from different fields. The massive new data sources resulting from human interactions with the internet offer a better understanding for the profound influence of external information on complex financial systems [31,32,33,34,35,36,37,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…To sum up, most of the research in this field address the predictive power of social media problem and the differences appear in information sources, their extracted features, and also the predictive methods and the values to be predicted. [7] have shown that trading volumes of stocks traded in NASDAQ-100 are correlated with their query volumes (i.e., the number of users requests submitted to search engines on the Internet). Gunduz and Cataltepe [22] proposed a forecasting method which combines the analysis of news articles from Turkish finance websites, the extraction of feature vectors and stock prices to predict future market movements.…”
Section: Related Workmentioning
confidence: 99%
“…Recent work prove that Web search volume can predict the values of some economic indicators. For instance, Bordino et al [9] show that daily trading volumes of NASDAQ-100 stocks are correlated with daily volumes of queries about the same stocks. Ettredge et al [10] use search logs to predict the job market while Choi and Varian [11] show how Google trends may be used to forecast unemployment levels, car and home sales, and disease prevalence in near real-time [11].…”
Section: Related Workmentioning
confidence: 99%